Immune response and innervation signatures in aseptic hip implant loosening - Daniel Marques Vasconcelos (2016)
Background: Aseptic loosening (AL) of hip prosthesis presents inflammation and pain as sign and symptom similarly to arthritis pathologies. Still, the immune and innervation profiles in hip AL remain unclear and their interplay is poorly explored. Herein, local tissue inflammatory response, sensory and sympathetic innervation as well as associated local mediators were assessed in hip joint microenvironment underlying AL and compared to osteoarthritis (OA). Methods: Histopathological analysis, immune cells (macrophages, T, B cells and PMNs) as well as sensory and sympathetic nerve fibers (SP+, CGRP(+), TH+) distribution and profiles were analyzed on tissues retrieved from patients with failed hip prostheses due to AL (n = 20) and hip OA (n = 15) by immunohistochemistry. Additionally, transcriptional levels of pro-inflammatory cytokines (TNF-alpha, IL-1 beta, IL-6, IL-12a, iNOS), anti-inflammatory cytokine (IL-10), osteoclastic factor (RANKL) and bone remodeling factor (TGF-beta 1) were locally evaluated by qRT-PCR. Serum TGF-beta 1 levels were assessed preoperatively by ELISA. Results: Histopathological analysis revealed that tissues, aseptic interface membranes of AL patients had distinct tissue architecture and immune cells profile when compared to OA synovial tissues. Macrophages, T cells and B cells showed significant differences in tissue distribution. In OA, inflammation is mostly confined to the vicinity of synovial membrane while in AL macrophages infiltrated throughout the tissue. This differential immune profile is also accompanied with a distinct pattern of sensory and sympathetic innervation. Importantly, in AL patients, a lack of sympathetic innervation aseptic interface membranes without compensation mechanisms at cellular levels was observed with simultaneous reorganization of sensorial innervation. Despite the different histopathological portrait, AL and OA patients exhibited similar transcriptional levels of genes encoding key proteins in local immune response. Nevertheless, in both pathologies, TGF-beta 1 expression was prominent in sites where the inflammation is occurring. However, at systemic level no differences were found. Conclusion: These findings indicate that AL patients exhibit different local inflammatory response and innervation signatures from OA patients in hip joint. These insights shed the light on neuro-immune interplay in AL and highlight the need to better understand this crosstalk to unravel potential mechanisms for targeted-therapies to improve hip joint lifetime and treatment.